The relationship between environmental ethics literacy and the caracteristics of environmental awareness of biology pre-service teachers - Hudha, Atok Miftachul; Aini, Firda; Miharja, Fuad Jaya (Universitas Negeri Jakarta, 2024)
Behavior that damages the environment can be changed through knowledge, because knowledge can influence a person's attitude in protecting theenvironment. This research aims to analyze the relationship between environmental ethics literacy and environmental awareness in prospective biology teacher students. The research was conducted on Biology Education students at